2013
DOI: 10.1161/atvbaha.113.300902
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Stem Cells in Vein Grafts Display Multilineage Potential That Contributes to Neointimal Formation

Abstract: Interestingly, these resident progenitor cells have been demonstrated to differentiate into a variety of cell types, including those of the vascular lineage, in response to specific culture conditions in vitro. 13 Although seminal studies implicate the © 2013 American Heart Association, Inc. Objective-This study was designed to carry out the characterization of stem cells within the adventitia and to elucidate their functional role in the pathogenesis of vein graft atherosclerosis. Approach and Results-A mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 48 publications
4
82
0
Order By: Relevance
“…Further analyses of their mouse vein graft model showed that remodeling adventitia contained a significant number of adventitial Sca-1 + cells in close proximity to vasa vasorum, ≈5% to 10% of which could form primary colonies in culture and were heterogeneous in size and morphology, suggesting different subpopulations of Sca-1 + progenitor cells. 62 These adventitia-derived cells possessed multipotent differentiation capacity giving rise to adipocytes, osteoblasts, chondrocytes, and SMCs under specific culture conditions, with the latter found to be dependent on integrin/collagen IV interactions. Moreover, Sca-1 + cells were also isolated from neointimal lesions and these too could be induced toward EC and SMC lineages in culture.…”
Section: Vascular Wall Smooth Muscle Progenitor Cellsmentioning
confidence: 95%
See 4 more Smart Citations
“…Further analyses of their mouse vein graft model showed that remodeling adventitia contained a significant number of adventitial Sca-1 + cells in close proximity to vasa vasorum, ≈5% to 10% of which could form primary colonies in culture and were heterogeneous in size and morphology, suggesting different subpopulations of Sca-1 + progenitor cells. 62 These adventitia-derived cells possessed multipotent differentiation capacity giving rise to adipocytes, osteoblasts, chondrocytes, and SMCs under specific culture conditions, with the latter found to be dependent on integrin/collagen IV interactions. Moreover, Sca-1 + cells were also isolated from neointimal lesions and these too could be induced toward EC and SMC lineages in culture.…”
Section: Vascular Wall Smooth Muscle Progenitor Cellsmentioning
confidence: 95%
“…60 Evaluation of adventitial Sca-1 + cells seeded onto decellularized vascular scaffolds in a bioreactor system revealed that their migratory ability was mediated by the stromal cell-derived factor-1/CXCR4 chemokine axis and their SMC differentiation potential via signaling through epidermal growth factor receptor, followed by activation of extracellular signal-regulated kinase 1/2 and nuclear translocation of β-catenin. 61,62 Interestingly, the drug sirolimus was shown to augment both progenitor cell migration and differentiation through these respective pathways, raising a new potential mechanism for restenosis formation after drug-eluting stent treatment. 61 In addition to adventitial progenitor cells, distinct subpopulations of mural SPCs have also been identified in the media of blood vessels.…”
Section: Vascular Wall Smooth Muscle Progenitor Cellsmentioning
confidence: 99%
See 3 more Smart Citations